Book ‘transforming urban transport: the ethics, politics, and practices of sustainable mobility’ review - Bruun, Eric (Transport, 2013)
Book ‘transforming urban transport: the ethics, politics, and practices of sustainable mobility’ review. Transport, 28(2), pp. 214-216First Published Online: 16 Jul 2013